2020
DOI: 10.21203/rs.2.24060/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TMEM100 negatively regulated by microRNA-106b facilitates cellular apoptosis by repressing survivin expression in NSCLC

Abstract: Background Non-small-cell lung cancer (NSCLC) is a common malignant tumor. Nevertheless, the 5-year survival rate of NSCLC patients remains poor. Thus, finding critical factors involved in regulating the progression of NSCLC is important for providing potential treatment targets. Methods CCK-8, colony formation, caspase-3 activity, luciferase reporter assay, and western blot assays were utilized in this study. Results We found that TMEM100 was significantly downregulated in NSCLC tissues compared with paired p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…TMEM100 is highly conserved among vertebrates, including mammals, zebrafish and chickens, and it is structurally unique from any known family of proteins [ 9 ]. It has been reported that TMEM100 is associated with cancer tumorigenesis and progression [ 10 ]. Han et al [ 11 ] showed that the expression of TMEM100 was significantly decreased in non-small cell lung cancer (NSCLC) tissues, while TMEM100 overexpression in NSCLC cell lines could inhibit cell proliferation, invasion and migration.…”
Section: Introductionmentioning
confidence: 99%
“…TMEM100 is highly conserved among vertebrates, including mammals, zebrafish and chickens, and it is structurally unique from any known family of proteins [ 9 ]. It has been reported that TMEM100 is associated with cancer tumorigenesis and progression [ 10 ]. Han et al [ 11 ] showed that the expression of TMEM100 was significantly decreased in non-small cell lung cancer (NSCLC) tissues, while TMEM100 overexpression in NSCLC cell lines could inhibit cell proliferation, invasion and migration.…”
Section: Introductionmentioning
confidence: 99%